PENDIDIKAN ISLAM DI KOTA PALU:(Perspektif Historisitas, Kelembagaan dan Peranan) - Arifuddin M Arif (Paedagogia: Jurnal Pendidikan, 2018)
Islamic education in the Palu valley grew and developed along with the entry and development of Islam in the city of Palu since 1650 (XVII century). Institutionally, Islamic education grows and develops through informal, semi-formal, formal, and formal education channels organized by Islamic community organizations, foundations, and the government. Islamic education which was born along with the coming of Islam itself in the valley of Palu, even though at first it was in a very simple form, until institutionalization was enough to color the diversity of the people of Palu City while respecting the culture and wisdom of the community. Islamic education in the city of Palu, has played its function and role in accordance with the demands of the community and its era, especially in fostering community fervor especially the Muslim community in the city of Palu.